Supporting stroke survivors to meet their personal rehabilitation needs in community-based arm rehabilitation: development of initial programme theories to explore what may work for whom, how and under what circumstances - Schnabel, Stefanie; van Wijck, Frederike; Kidd, Lisa (Frontiers in Neurology, 2023)
Objective: This study explored what worked for whom, how and under what circumstances in a community-based augmented arm rehabilitation programme that was designed to enable stroke survivors to meet their personal rehabilitation needs. Design: A mixed methods realist-informed study of data from a randomised controlled feasibility trial, comparing augmented arm rehabilitation after stroke with usual care. The analysis was designed to develop initial programme theories and refine these through triangulation of qualitative and quantitative trial data. Participants with a confirmed stroke diagnosis and stroke-related arm impairment were recruited from five health boards in Scotland. Only data from participants in the augmented group were analysed. The augmented intervention comprised evidence-based arm rehabilitation (27 additional hours over six weeks) including self-managed practice, and focused on individual rehabilitation needs identified through the Canadian Occupational Performance Measure (COPM). The COPM indicated to which extent rehabilitation needs were met following the intervention, the Action Research Arm Test provided data on changes in arm function, and qualitative interviews provided information about the context and potential mechanisms of action. Findings: Seventeen stroke survivors (11 males, age range 40 – 84 years, NIHSS median (IQR) 6 (8)) were included. Median (IQR) COPM Performance and Satisfaction scores (min.1-max.10) improved from pre-intervention 2 (5) to post-intervention 5 (7). Findings suggested that meeting rehabilitation needs was facilitated by strengthening participants’ sense of intrinsic motivation (through grounding exercises in everyday activities linked to valued life roles, and enabling them to overcome barriers to self-managed practice), and via therapeutic relationships (through trust and expertise, shared decision-making, encouragement and emotional support). Collectively, these mechanisms enabled stroke survivors to build confidence and gain mastery experience necessary to engage in new self-managed practice routines. Conclusion: This realist-informed study enabled the development of initial programme theories to explain how and in what circumstances the augmented arm rehabilitation intervention may have enabled participants to meet their personal rehabilitation needs. Encouraging participants’ sense of intrinsic motivation and building therapeutic relationships appeared instrumental. These initial programme theories require further testing, refinement, and integration with the wider literature.